A High‐k Fluorinated P(VDF‐TrFE)‐g‐PMMA Gate Dielectric for High‐Performance Flexible Field‐Effect Transistors. (1st December 2017) - Shin, Eul‐Yong; Cho, Hye Jin; Jung, Sungwoo; Yang, Changduk; Noh, Yong‐Young
Abstract: A newly synthesized high‐ k polymeric insulator for use as gate dielectric layer for organic field‐effect transistors (OFETs) obtained by grafting poly(methyl methacrylate) (PMMA) in poly(vinylidene fluoride‐trifluoroethylene) (P(VDF‐TrFE)) via atom transfer radical polymerization transfer is reported. This material design concept intents to tune the electrical properties of the gate insulating layer (capacitance, leakage current, breakdown voltage, and operational stability) of the high‐ k fluorinated polymer dielectric without a large increase in operating voltage by incorporating an amorphous PMMA as an insulator. By controlling the grafted PMMA percentage, an optimized P(VDF‐TrFE)‐ g ‐PMMA with 7 mol% grafted PMMA showing reasonably high capacitance (23–30 nF cm −2 ) with low voltage operation and negligible current hysteresis is achieved. High‐performance low‐voltage‐operated top‐gate/bottom‐contact OFETs with widely used high mobility polymer semiconductors, poly[[2, 5‐bis(2‐octyldodecyl)‐2, 3, 5, 6‐tetrahydro‐3, 6‐dioxopyrrolo [3, 4‐c]pyrrole‐1, 4‐diyl]‐ alt ‐[[2, 2′‐(2, 5‐thiophene)bis‐thieno(3, 2‐b)thiophene]‐5, 5′‐diyl]] (DPPT‐TT), and poly([ N, N ′‐bis(2‐octyldodecyl)‐naphthalene‐1, 4, 5, 8‐bis(dicarboximide)‐2, 6‐diyl]‐ alt ‐5, 5′‐(2, 2′‐bithiophene)) are demonstrated here. DPPT‐TT OFETs with P(VDF‐TrFE)‐ g ‐PMMA gate dielectrics exhibit a reasonably high field‐effect mobility of over 1 cm 2 V −1 s −1 with excellent operational stability. Abstract : A high‐ k polymeric insulator is developed by chemically grafting poly(methylmethacrylate) (PMMA) to poly(vinylidenefluoride‐trifluoroethylene) (P(VDF‐TrFE)) for use as a gate dielectric layer in organic field‐effect transistors (OFETs). A device with an optimized P(VDF‐TrFE)‐g‐PMMA ratio (7% grafted ratio) shows a high capacitance of 23‐30 nF cm −2 . Poly[[2, 5‐bis(2‐octyldodecyl)‐2, 3, 5, 6‐tetrahydro‐3, 6‐dioxopyrrolo[3, 4‐c]pyrrole‐1, 4‐diyl]‐alt‐[[2, 2′‐(2, 5‐thiophene)bis‐thieno(3, 2‐b)thiophene]‐5, 5′‐diyl]] (DPPT‐TT) OFETs with P(VDF‐TrFE)‐ g ‐PMMA exhibit high field‐effect mobility of over 1 cm 2 V −1 s −1 .